PRAWO ŁASKI NA POZIOMIE STANOWYM W USA - Kwiatkowski, Wojciech (Zeszyty Prawnicze, 2017)
The Right of Clemency at the State Level in the United States Summary The article discusses the core issues related to state-level clemency in the United States of America. This power is deeply rooted in American history. At this level clemency often serves as an important mechanism of checks and balances on the state judiciary; it enables error-correction in a state criminal justice system, it may afford relief from undue harshness, and it helps to ensure that the state justice system is tempered. Although it is not required by the federal constitution, each state has a constitutional provision addressing clemency. This article points out that an important difference compared with solutions at the federal level is that the power to exercise clemency at the state level is vested in either the governor, an executive clemency board, or a combination thereof, so an important part of the study was to determine the advantages and disadvantages of each of these solutions. Another important aspect of the study was to identify the determinants affecting the regulation and application of state clemency. The article also discusses (I) some legal methods to limit the power to pardon and (II) regulations which determine the transparency of the whole procedure.